PENILAIAN KINERJA KOPERASI SERBA USAHA (KSU) â€œGALANG DANA MANDIRIâ€ KOTA MADIUN BERDASARKAN PERATURAN MENTERI NEGARA KOPERASI DAN USAHA KECIL DAN MENENGAH NO. 14/PER/M.KUKM/XII/2009. - Putra, Ryo Prayoga Purnama; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Microfinance Institutions (MFIs) non-banks in Indonesia play an important role in economic growth, one of which is a cooperative. Cooperative support SMEs to obtain funds to be able to continue their business. This research aim to analyze the financial healt employee cooperative non - financial in Koperasi Serba Usaha (KSU)